Health Halo Effect and Mandela Effect. An Experimental Approach on Packaging Nutrient Content Claims - BERA, Fabia-Roberta; GRIVASĂ, Oana-Mihaela; IANCU, Ioana (Styles of communication, 2022)
Health concerns are the main reason for healthy product purchasing. Likewise, the packaging plays an important role in the decision-making process. The present paper investigates the health halo effect and the Mandela effect produced by the nutrient content claims on the packaging of food products (chocolate). The main objectives are: to determine if the respondents remember ingredients and claims that are not actually listed on the packaging, to investigate if the existence of nutrient content claims on the packaging determines a more positive perception on the healthfulness of the product and a higher purchase intention, and to explore if risk-avoidance claims (Low sugar and Cholesterol free), in comparison with benefit related claims (Vitamin A and High in fibers) are more likely to determine a more positive healthfulness perception of the product and a higher purchase intention. A 1x3 survey-based experiment has been conducted on 160 young adults in Romania. The results show that, regardless of the situation, subjects tend to remember a high number of ingredients and claims that are not actually written on the packaging. The nutrient claims, in comparison with the lack of them, play an important role in shaping a positive healthfulness perception and a higher purchase intention. Finally, the risk-avoidance claims seem to have a more positive effect.